Budgeting as a Method of Cost Management Using a Residential Community as an Example - Bartłomiej Juras; Małgorzata Czerny (Studia i Materiały)
This article discusses the role of budgeting as a method of cost management in a housing community in the Greater Poland region, during the period of 2011–2015. General research methods were used, such as analysis of the budgets of the housing community, as well as deductive reasoning and inductive reasoning for conclusions. The analyses contain also cost trends in the examined period, some average costs in the period, cost division into groups, costs per capita, per apartment, etc., but focus mostly on variations between budget plans and their implementation. The analysis of the budgets and their implementation in 2011–2015 shows that budgeting is successfully used to manage a community’s finances. Budgeting as a cost management instrument allowed the community to achieve significant reductions in certain categories of costs.